Analisis Yuridis Perjanjian Kerjasama Antara Perusahaan Properti Dengan Perbankan Terhadap Pembiayaan Perumahan Dengan KPR (Studi Di PT. Cukat Trengginas Arians) - Septian Fujiansyah (Universitas Islam Sumatera Utara, 2021)
The provision of KPR facilities by the Bank, sometimes through the property company as a housing provider. The cooperation developed by the Bank and the property company is regulated in a cooperation agreement deed which contains clauses regarding everything related to the implementation of the cooperation. The problem discussed in this study is whether the implementation of the cooperation agreement between the property company PT. Cukat Trengginas Arians with PT. BTN (Persero) regarding housing finance with KPR is in accordance with the law of agreements and banking in Indonesia, how to resolve disputes if one of the parties violates the cooperation agreement between the property company PT. Cukat Trengginas Arians with PT. BTN (Persero) regarding housing finance with KPR, how the legal protection of the parties in the cooperation agreement between the property company PT. Cukat Trengginas Arians with PT. BTN (Persero) on housing finance with KPR.The implementation of the cooperation agreement between the property company (PT. Cukat Trengginas Arians) and PT. BTN (Persero) for housing finance with KPR which is the legal requirement for a cooperation agreement has been fulfilled and is in accordance with the agreement law and banking in Indonesia. The dispute settlement by one of the parties violates the cooperation agreement between the property company (PT. Cukat Trengginas Arians) and PT. BTN (Persero) is through both litigation and non-litigation channels. In its implementation, PT. BNI (Persero) and PT. Cukat Trengginas Arians prioritizes dispute resolution through non-litigation channels. Legal protection for the parties in the cooperation agreement between the property company (PT. Cukat Trengginas Arians) and PT. BTN (Persero) regarding the implementation of the housing finance cooperation agreement with KPR has been fully stated in the cooperation agreement, where each party has their respective rights and obligations and the legal protection is adjusted to the default made. Keywords: KPR, Cooperation Agreement, Property